Delivery Laundry System: The Development of Laundry Web-Based System for UTHM Student to Make Laundry More Convenient - Mohd Suhaimi Md Yasin; Kamaruzaman, Khairina Batrisyia; Tarmizi, Alya Humaira Syahmi; Mazlan , Puteri Amalin Alieyssa (Multidisciplinary Applied Research and Innovation, 2023)
People, particularly students, are unable to perform household tasks such as cooking, cleaning, and laundry in this technological age. Because they don’t have time to do their own laundry, they may just wear the same dirty clothing without cleaning them. Laundry delivery services are getting increasingly popular at this time. One of the reasons for the emergence of this laundry delivery business is the scarcity of washing machines for so many students. Students only wash their laundry in their leisure time, which is only on weekends because it is the only day when they do not have any classes or activities. So this concept will undoubtedly save students time by assisting them in washing their laundry and delivering it to their door. The goal of this project is to create a user-friendly and effective laundry delivery system.